2018
DOI: 10.5603/cj.a2017.0078
|View full text |Cite
|
Sign up to set email alerts
|

What determines the quality of life of adult patients after Fontan procedure?

Abstract: (Cardiol J 2018; 25, 1: 72-80)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…13,14 Almost all studies of physical capacity and performance in young Fontan patients have shown a reduced maximal heart rate, and many have suggested this to be a limiting factor for physical performance and tolerance. [15][16][17] Repeated heart surgery early in life has been suggested to injure the heart's autonomous nervous system and impair sinoatrial response to exercise. 18 A recent report with measurements of stroke volume during exercise in a small number of adult Fontan patients suggests that the main limiting factor for cardiac output and maximal exercise capacity is impaired diastolic filling and stroke volume by the ventricle rather than heart rate.…”
mentioning
confidence: 99%
“…13,14 Almost all studies of physical capacity and performance in young Fontan patients have shown a reduced maximal heart rate, and many have suggested this to be a limiting factor for physical performance and tolerance. [15][16][17] Repeated heart surgery early in life has been suggested to injure the heart's autonomous nervous system and impair sinoatrial response to exercise. 18 A recent report with measurements of stroke volume during exercise in a small number of adult Fontan patients suggests that the main limiting factor for cardiac output and maximal exercise capacity is impaired diastolic filling and stroke volume by the ventricle rather than heart rate.…”
mentioning
confidence: 99%
“…SND is a common, late complication post-Fontan surgery [ 18 , 23 ]. Patients with Fontan circulation reportedly experience a reduced quality of life, compared to healthy controls [ 24 ], with arrhythmia and chronotropic incompetence shown to be predictive of the level of health-related quality of life impairment in these patients [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional health assessment, using the SF-36, was completed in all 39 patients and 40 controls. Scores were analysed according to published guidelines described previously [ 10 ]. A score between 0 and 100 was calculated for each domain.…”
Section: Methodsmentioning
confidence: 99%